2019
DOI: 10.1002/kpm.1614
|View full text |Cite
|
Sign up to set email alerts
|

Social capital, knowledge quality, knowledge sharing, and innovation capability: An empirical study of the Indian pharmaceutical sector

Abstract: Management of technology and innovation is a topic that has been subjected to a lot of discussions by the academicians and practitioners alike. Furthermore, researchers have emphasized the importance of the role that knowledge management/knowledge sharing can play in promoting innovation in an organization. The purpose of this paper is to evaluate the role of social capital and knowledge sharing in achieving innovation capability of an organization. It also discusses the role that knowledge quality might play … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 136 publications
(173 reference statements)
1
20
0
3
Order By: Relevance
“…The first hypothesis in this study is that knowledge sharing has a positive and significant effect on innovation ability. Several previous studies support these results by Lo & Tian (2020;Kurniawan et al 2020;Ganguly et al 2020;Le & Lei, 2019;Lam et al 2021). The analysis results in this study support the first hypothesis and prove that knowledge sharing can positively and significantly impact the ability to innovate in modern cafes and restaurants in Yogyakarta.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…The first hypothesis in this study is that knowledge sharing has a positive and significant effect on innovation ability. Several previous studies support these results by Lo & Tian (2020;Kurniawan et al 2020;Ganguly et al 2020;Le & Lei, 2019;Lam et al 2021). The analysis results in this study support the first hypothesis and prove that knowledge sharing can positively and significantly impact the ability to innovate in modern cafes and restaurants in Yogyakarta.…”
Section: Discussionsupporting
confidence: 62%
“…The importance of knowledge management was also highlighted by research on 97 pharmaceutical industry employees in India regarding knowledge quality, explicit and implicit knowledge sharing, and innovation capabilities. The analysis results show that knowledge quality and detailed and tacit knowledge sharing significance affect the innovation ability of pharmaceutical companies in India (Ganguly et al 2020).…”
Section: Knowledge Sharing and Innovation Abilitymentioning
confidence: 97%
See 1 more Smart Citation
“…The knowledge sharing behaviour between members and departments in an organization has enormous benefits. The results showed that knowledge sharing can increase productivity [1]; jobsatisfaction [2]; creativity [3]; innovation capability [4]; etc.…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge sharing can promote the accumulation and flow of knowledge, which is essential for the translation of individual knowledge to organizational knowledge ( Hooff and Ridder, 2004 ) and the generation of new knowledge. Therefore, it is positively related to employees’ creative behavior, innovation capability, and innovation performance ( Kim and Lee, 2013 ; Akhavan and Hosseini, 2016 ; Pian et al, 2019 ; Clercq and Pereira, 2020 ; Ganguly et al, 2020 ), which is also an important factor affecting employees’ IWB ( Akram et al, 2020 ; Asurakkody and Kim, 2020 ; Yasir et al, 2021 ). As mentioned above, knowledge sharing consists of two central processes: knowledge collecting and donating ( Hooff and Ridder, 2004 ).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%